Effect of Tacrolimus Once Daily XR on Variance of Blood Tacrolimus Concentrations in Comparison with Twice Daily Tacrolimus in Kidney Transplant Recipients - I Gde Raka Widiana; I Made Rama Putra; Stefany Adi Wahyuningrum (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2025)
Background: Variability of tacrolimus concentration in the plasma of recipients is associated with nephrotoxicity, acute rejection, and affects graft survival. Objective: To test the hypothesis that the coefficient variation of plasma tacrolimus in new tacrolimus XR (extended-release) once daily is lower than conventional twice daily. Methods: The study was conducted in two phases. Phase 1, a comparative observational analysis with a single-group crossover, comparing periods of divided-dose treatment with crossover to prolonged-dose treatment. Phase 2, a cross-sectional design, is used to correlate IVP and serum creatinine variation. Results: A total of 19 kidney post-transplant recipients were included. There was a significant difference in blood tacrolimus CoV between XR tacrolimus and divided dose therapy (22.22±7.39% vs 44.32±15.54%, p<0.001). A significant linear correlation was observed between blood tacrolimus CoV and serum creatinine CoV in all patients (r=0.74; r2= 0.54; b=1.15; p<0.001). Subgroup analysis revealed a significant correlation between blood tacrolimus CoV in divided dose tacrolimus therapy subgroup (r=0.58; r2= 0.33; p=0.02) but not in the XR group (r=0.06; r2= 0.004; p=0.84). Multivariate ANCOVA showed serum CoV was associated with CoV of blood tacrolimus (B=0.72; r2= 0.255; p=0.01). Furthermore, XR tacrolimus was associated with lower serum creatinine CoV (B= -20.7; r2=0.20; p=0.02). Conclusion: XR tacrolimus therapy produces significantly lower variance of blood tacrolimus concentrations in kidney transplant recipients. This variance is associated with serum creatinine variance, especially in divided-dose tacrolimus therapy. Serum creatinine variance is linked to variances in blood tacrolimus levels, and XR tacrolimus therapy is associated with lower serum creatinine variance.